A preliminary study of job satisfaction and motivation among the Malaysian primary healthcare professionals - Chew, Boon How; Ramli, Anis Safura; Omar, Mimi; Ismail, Irmi Zarina (Academy of Family Physicians of Malaysia, 2013)
Aim: This study aimed to examine the relationship between personal or work-based characteristics and job satisfaction and motivation in Malaysian primary healthcare professionals. Methods: This was a cross-sectional survey conducted during the 15th Family Medicine Scientific Conference in June 2011 using the Warr-Cook-Wall scales. The questionnaires included demography and work-related items and were self-distributed and returned at the end of the conference. Independent risk factors were identified using multiple linear regressions. Results: A total of 149 conference participants completed the survey, with a response rate of 33.1%. They were mainly females (85.2%), Malay (83.2%), and married (83.9%) in almost equal proportions of practice location (urban 57.8% and rural 42.2%). Majority of them were working at community-based health clinics (74.0%) and in public sectors (94.4%). The respondents were mainly doctors (91.4%). The mean age of the participants was 39.1 years (SD 8.0), with a mean duration of service of 9 years (SD 6.9). Family medicine specialty (FMSt) residents had lower job satisfaction (B = -8.0, 95% CI -14.61 to -1.40, p = 0.02). Family medicine specialists (FMSs) had higher satisfaction with working conditions (B = 1.95, 95% CI 0.50 to 3.41, p = 0.01). A male worker had on average 2.8 (95% CI -4.7 to -0.9, p = 0.005) lower points in the total intrinsic job motivation scale. There was a positive relationship between the duration of working and job motivation (B = 0.10, 95% CI 0.004 to 0.2, p = 0.04). Conclusion: FMSt residents might have the least job satisfaction, but FMSs were generally satisfied with their working conditions regardless of the location of their clinics. Men and those who were novice in primary healthcare may need more support for motivation.